Success Predictors of Adjuvant Chemotherapy in Node-Negative Breast Cancer Patients Under 55 years1 - Emiel A. M. Janssen; Paul J. van Diest; Håvard Søiland; Einar Gudlaugson; Arne Nysted; Feja J. Voorhorst; Jan B. Vermorken; Jon-Arne Søreide; Jan P. A. Baak (Cellular Oncology)
Background: Adjuvant systemic chemotherapy (ASCT) in lymph node-negative breast (LN−) cancers improves survival. The majority of (LN−) patients receive ASCT when the St. Gallen criteria or its modifications are used, as accurate identifiers which patients benefit from ASCT are lacking. This may imply over-treatment in many patients. Aim: To evaluate which patients or primary tumor factors predict ASCT success. Material and method: Retrospective analysis by single and multivariate survival analysis of clinical and tumor characteristics in (LN−) breast cancers <55 years, related to ASCT (n = 125) or-not (n = 516). Results: The two patient groups did not differ in age, tumor diameter, grade, type, number of mitoses and other factors. Fourteen-year survival for the ASCT and non-ASCT patients was 83% and 74% (Hazard Ratio = HR = 0.33; p < 0.0001, 9% absolute = 12% relative difference). Subgroup analysis showed that the recurrence-free survival = RFS of ASCT treated vs. non-treated patients differed in patients with grade 1 cancers (p = 0.008), grade 2 cancers (p = 0.004), grades 3 (p = 0.02), tumors under and ≧2 cm (p = 0.001 and 0.0002), oestrogen receptor-positive or -negative tumors (p = 0.003, 0.04), MAI < 10 and ≧10 (p = 0.005, 0.003) and fibrotic focus absent (p = 0.002). With multivariate analysis the most important predictor of ASCT effect was the MAI. In patients with slowly proliferating tumors (MAI < 3) no advantage was found between patients treated-or-not with adjuvant chemotherapy (RFS = 92% and 91%, p = 0.13, p = 0.63 for overall survival), contrasting those with MAI ≧ 3 (p = 0.0001; HR = 0.32, 95% CI 0.18–0.58). Conclusion: MAI is the strongest predictor of adjuvant systemic chemotherapy success. In patients with MAI < 3 (31% of all patients), ASCT does not improve survival.